The Existence of Cultural Relativism and Its Approach on Different Function of Human Capabilities: A Case from Indonesia - Surya Oktaviandra (Nurani Hukum, 2022)
The universal notion of Human Rights evokes our curiosity on how the same value can be adopted by different time, space, place, and culture. In another side, Capability Approach helps us conceiving how the same human capabilities can be interpreted differently by different functioning. This research aims to serve a different perspective on using Capability Approach to fathom the fulfillment of Human Rights particularly by presenting the relativism of culture around the world by utilizing socio-legal approach. Furthermore, it will discuss evidence from Indonesia, particularly in land acquisition and politic participation, as example how its civilization leads to the deviation of Human Right`s universality. The result of this study shows key finding that the government or society which can be apprehended violates human rights, will be seen reasonably respect human rights for its people if the insight of cultural relativism can be understood.